Students’ Strategy in Translating English Text Into Bahasa Indonesia (A Case Study at Agrotechnology Department University of Bina Insan Lubuklinggau) - herlina, Herlina; Riance, Astri (Edu-Ling: Journal of English Education and Linguistics, 2024)
This research is dialed to present students’ strategy in translating English text into bahasa Indonesia. The method research used descriptive qualitative. The subject of this research was third and sixth semester students of Agrotechnology Department at University of Bina Insan Lubuklinggau. Collecting data was taken from the data analysis of questionnaire and interview. The result showed that based on the persentages of questionnaire, it was concluded that the total score of students used from word for word translation, literal translation and free translation were 1.555 (one thousands five hundred and fifty five). While, 521 total scores of students in word for word translation, the next 507 total scores of students in literal translation, and for the students in free translation, the total score was 527. Furthermore, the result of interview showed that the analysis of students’ difficulties in translating English text was between linguistic factor and culture factor. The linguistic  problem involved grammar, less of vocabulary and the meaning of each word. Culture problem involved related to form of different situation. In conclusion, there are four categories of students’ difficulties in translation, they are: (1) difficult to understand the meaning of word that not find in dictionary; (2) difficult to translate the idiomatic phrases and collide with culture; (3) difficult to translate long sentence or long paragraf.